Effect of Plating Medium on Heat Activation Requirement of Clostridium botulinum Spores - Montville, Thomas J. (1981)
Clostridium botulinum 62A and ATCC 25763 spores required heat activation for maximum colony formation when plated on reinforced clostridial agar (BBL Microbiology Systems) but not when plated on botulinum assay medium. Spores from strains B-aphis and 53B did not exhibit heat activation when plated on either medium.